Correlation between Zinc and Folic Acid Intake with Hemoglobin Levels in Pregnancy - Eka Darmayanti Putri Siregar; Arni Amir; Nuzulia Irawati (Institute of Computer Science (IOCS), 2022)
The deficiency of micronutrients and anemia are nutritional problems in pregnancy. WHO in 2019 and Riskesdas in 2018 reported that anemic pregnant women in Indonesia were 44.2% and 48.9%. Public Health Service also reported there was an increased prevalence of this problem in West Sumatra and Padang City in 2019 which was 18.1% and 11.2%. Micronutrient deficiency affected the hemoglobin (Hb) level, which is one of the indicators marking anemia in pregnancy. The objective was to determine the correlation between zinc and folic acid with hemoglobin levels in the third trimester of pregnancy. This analytical cross-sectional research was held in the Health Center and laboratory of Lubuk Kilangan on May-July 2022. The population and samples were 64 third-trimester pregnant women with total sampling. Intake data were collected through interviews using the Food Frequency Questionnaire (FFQ). Hemoglobin levels were examined by a hematology analyzer. Pearson correlation was used to identify the correlation of the variables (P< 0.05) . The mean levels of zinc and folic acid intake and hemoglobin levels were 7.35 mg, 215.56 mcg, and 11.08 g/dL. There was a positive correlation between zinc (p=0,015) and folic acid (p=0.004) with hemoglobin levels in the third trimester of pregnancy.